Impact of Waste Management on Surface Water and Soil Pollution on the Right Bank of the Congo River in the Brazzaville Agglomeration (Republic of Congo) - Orline Lesley, Mbianda Nfong-Ya; Jean de Dieu, Nzila; Raison Félicien, Louzayadio Mvouezolo; Justin Clair, Bonazaba Milandou Longin; Isidore, Nguelet – Moukaha; Patience, Wando Georgy; Maurille, Ouamba Jean; Pépin, Aina Martin (European Scientific Journal, ESJ, 2024)
Situated on the right bank of the Pool Malébo, in the Congo River basin, the city of Brazzaville is rich in potential water resources. This resource is being polluted by human practices that are deteriorating the quality of the soil and, consequently, the quality of the water. The aim of this study is therefore to list the activities carried out by the population around watercourses in order to get an idea of how waste is managed and its impact on water and soil quality. The survey sample was selected on the basis of zones of influence located between 250 m and 750 m around watercourses. The survey form was drawn up using Sphinx Plus2-Edition Lexica-V5. The data from the surveys was entered into the same software, then transferred to Excel for processing in order to produce the graphs. 880 people were surveyed, the most dominant age group being between 25 and 48 years old, i.e. a rate of 66%; the female sex being the most representative with a rate of 54%. The average age of the respondents was lower secondary school, and they were generally employed in the private sector. Commercial activities (restaurants/bars, pharmacies, grocery stores/butchers, markets, etc.) are the most common economic activity, with a rate of around 70%; 59% of these activities are located close to or very close to the watercourse (750 - 1000 m). The activities that contribute to soil degradation, and consequently water degradation, in the city of Brazzaville are: 59% the dumping of household waste and/or wastewater on the ground and 32% uncontrolled urbanization. The study shows that soil and water pollution in Brazzaville is caused by poor management of household waste and uncontrolled urbanization.